Sliding-mode control design of a slotless self-bearing motor - Vo Duc Nhan; Nguyen Xuan Bien; Nguyen Quang Dich; Vo Thanh Ha (Bulletin of Electrical Engineering and Informatics, 2022)
Scientists have explored and are studying a slotless self-bearing motor, an electric motor with a magnetically integrated bearing function. As a single actuator, it can provide both levitation and rotation. This article will show a slotless self-bearing motor with a stator that does not have an iron core but six-phase coils. A permanent magnet and an enclosed iron yoke make up the rotor. To regulate the rotational speed and radial location of the rotor, magnetic forces created by the interaction between stator currents and the magnetic field of permanent interest are investigated. This research also includes a slotless-bearing motor mathematical model and control approach. This motor is investigated by combining an AC motor with a magnetic drive to achieve the essential design criterion and low cost. The magnetic force and moment characteristics are theoretically analyzed, and a control technique is proposed. Sliding-mode control (SMC) is a control method that is simple, effective and utilized to serve the control system for approaching the reference value, as stated in this study. It's also commonly used to manage the motor's position and speed. The findings were built and evaluated using MATLAB/Simulink confirmed analytical results to prove the recommended control approach.